2015
DOI: 10.1093/abbs/gmv059
|View full text |Cite
|
Sign up to set email alerts
|

A lentiviral vector-based therapeutic vaccine encoding Ag85B-Rv3425 potently increases resistance to acute tuberculosis infection in mice

Abstract: Few treatment options for multidrug-resistant tuberculosis (TB) and extensively drug-resistant TB call attention to the development of novel therapeutic approaches for TB. Therapeutic vaccines are promising candidates because they can induce antigen-specific cellular immune responses, which play an important role in the elimination of Mycobacterium tuberculosis (MTB). In this study, a novel lentiviral vector therapeutic vaccine for delivering MTB-specific fusion protein Ag85B-Rv3425 was constructed. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…As our previously reported, fusion protein Ag85B-Rv3425 is proved to be an effective multiple epitopes antigen (11,13). In our study, we found that recombinant plasmid A3-Vec, like lentivirus delivered A3 (11), could induce A3 fusion protein specific antibody IgG response, indicating that it could be expressed in mice and then recognized by immune system.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…As our previously reported, fusion protein Ag85B-Rv3425 is proved to be an effective multiple epitopes antigen (11,13). In our study, we found that recombinant plasmid A3-Vec, like lentivirus delivered A3 (11), could induce A3 fusion protein specific antibody IgG response, indicating that it could be expressed in mice and then recognized by immune system.…”
Section: Discussionsupporting
confidence: 61%
“…As a novel immunotherapy strategy, therapeutic vaccine has been successful for TB control not only in latent TB infection model but also in acute infection model (11,12).…”
Section: Tuberculosis (Tb) a Worldwide Infectious Disease Caused Bymentioning
confidence: 99%
See 2 more Smart Citations
“…Lentiviruses are widely used in basic biology and gene therapy due to their efficient gene delivery capabilities [109]. They have also been shown to elicit robust cellular immunity and improve mucosal immunity, making them a potential vector for TB vaccines [97,110]. However, lentivectors retain broad tropism, which could impact their safety.…”
Section: Novel Viral Vectors For Tb Vaccines In Developmentmentioning
confidence: 99%